O cilindro apaixonado - Lourdes , Dayane Freitas de; Cruz , Florisvaldo Gonçalves da; Martin , Maria Sinforosa; Dan , Marlene Amaral de Matos; Carraro, Márcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf